2010
DOI: 10.1590/s0066-782x2010000100013
|View full text |Cite
|
Sign up to set email alerts
|

Ausência de descenso noturno se associa a acidente vascular cerebral e infarto do miocárdio

Abstract: Background: The arterial hypertension varies in according to the circadian cycle, presenting physiologic fall of blood pressure (BP) during sleep (dipping). The absence of this fall or its increase associates to higher incidence of targetorgan damages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In another study which was designed to investigate the hypertensive target organ damage difference between the dippers and non-dippers, left ventricular mass indexes were found to be significantly greater in patients with non-dipping BP profiles [21]. From the clinical point of view, the prevalence of the most undesirable consequences of atherosclerotic burden such as stroke and myocardial infarction were disclosed to be high in the absence of nocturnal dipping in BP [22]. Despite the presence of many reports evaluating the association between non-dipper hypertension and atherosclerosis/atherosclerosis-related diseases, few efforts have been made to investigate the underlying mechanisms so far.…”
Section: Discussionmentioning
confidence: 99%
“…In another study which was designed to investigate the hypertensive target organ damage difference between the dippers and non-dippers, left ventricular mass indexes were found to be significantly greater in patients with non-dipping BP profiles [21]. From the clinical point of view, the prevalence of the most undesirable consequences of atherosclerotic burden such as stroke and myocardial infarction were disclosed to be high in the absence of nocturnal dipping in BP [22]. Despite the presence of many reports evaluating the association between non-dipper hypertension and atherosclerosis/atherosclerosis-related diseases, few efforts have been made to investigate the underlying mechanisms so far.…”
Section: Discussionmentioning
confidence: 99%
“…A nocturnal dip (ND) was defined as a decrease in BP ≥ 10% from awake to sleep. 14 A WCE was considered present when an individual had a BP outside the control target when measured at the office, but a normal ABPM. However, if the BP was controlled in the office but elevated during the ABPM, the patient was classified as having a false control.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies have assessed BP levels with a single office BP measurement or even reported BP medication. Only a few studies have utilized ambulatory blood pressure monitoring, which presents better correlation with daily life blood pressure and hypertension-related target organ damage [10, 68]. …”
Section: Limitations Involved In This Associationmentioning
confidence: 99%